Healthy lifestyle and risk of breast cancer among postmenopausal women in the European Prospective Investigation into Cancer and Nutrition cohort study. Issue 11 (16th November 2014) - McKenzie, Fiona; Ferrari, Pietro; Freisling, Heinz; Chajès, Veronique; Rinaldi, Sabina; de Batlle, Jordi; Dahm, Christina C; Overvad, Kim; Baglietto, Laura; Dartois, Laureen; Dossus, Laure; Lagiou, Pagona; et al.
<x xml:space="preserve">Abstract</x> Breast cancer is the most common cancer among women and prevention strategies are needed to reduce incidence worldwide. A healthy lifestyle index score (HLIS) was generated to investigate the joint effect of modifiable lifestyle factors on postmenopausal breast cancer risk. The study included 242, 918 postmenopausal women from the multinational European Prospective Investigation into Cancer and Nutrition (EPIC) cohort, with detailed information on diet and lifestyle assessed at baseline. The HLIS was constructed from five factors (diet, physical activity, smoking, alcohol consumption and anthropometry) by assigning scores of 0–4 to categories of each component, for which higher values indicate healthier behaviours. Hazard ratios (HR) were estimated by Cox proportional regression models. During 10.9 years of median follow‐up, 7, 756 incident breast cancer cases were identified. There was a 3% lower risk of breast cancer per point increase of the HLIS. Breast cancer risk was inversely associated with a high HLIS when fourth versus second (reference) categories were compared [adjusted HR = 0.74; 95% confidence interval (CI): 0.66–0.83]. The fourth versus the second category of the HLIS was associated with a lower risk for hormone receptor double positive (adjusted HR = 0.81, 95% CI: 0.67–0.98) and hormone receptor double negative breast cancer (adjusted HR = 0.60, 95% CI: 0.40–0.90). Findings suggest having a high score on an index of combined healthy behaviours reduces the risk of developing breast cancer among postmenopausal women. Programmes which engage women in long term health behaviours should be supported.